The influence of transactional leadership style and transformational on organizational commitment with compensation as a moderating variable - Lukieto Cahyadi; Willy Cahyadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to determine the effect of transactional and transformational leadership styles on the commitment of stikes banalita Sudama Medan employees with compensation as a moderating variable. The research method used is quantitative data method. Data collection in this study was carried out by distributing questionnaires (questionnaires) to respondents. The analysis technique used in this study is the Multiple Linear Regression model. The results of the study show that the Transactional Leadership Style (X1) and the Transformational Leadership Style (X2) have a significant simultaneous effect on the Organizational Commitment variable (Y). Compensation (Z) is a moderating variable that influences the relationship between Transactional Leadership Style (X1) and Transformational Leadership Style (X2) and Organizational Commitment (Y). Variables Transactional Leadership Style (X1), Transformational Leadership Style (X2), and Compensation (Z) can explain the variable Organizational Commitment (Y) of 41.3%. Seeing the results of this study which shows that the provision of compensation strengthens the relationship of leadership style to organizational commitment, it is expected to continue to maintain compensation to always support employee performance which of course will also have a positive impact on the productivity of the Binalita Sudama College of Health, Medan.